Application of the discovery learning model assisted by wordwall educational games media to increase the learning motivation of grade 5 students - Wahyu Sulistiyowati (Universitas Sebelas Maret, 2022)
This report is motivated of low motivation of class V students at SDN 1 Karangnongko in learning science and harmony and ecosystem material. One alternative to help improve learning outcomes, the author made improvements through the application of the discovery learning model assisted by wordwall games. This report describes the implementation and results of learning improvement research on the use of the discovery learning model assisted by wordwall games. The research used the PTK method which was carried out in 2 cycles. Each cycle consists of four stages including planning, implementation, observation and reflection. The subjects of this research were fifth grade students at SDN 1 Karangnongko. The instrument used in this research is qualitative data. Qualitative data was obtained through student and teacher activity observation sheets. The results of the research show that there is an increase in learning outcomes along with increased activity, motivation and increased student learning. Thus, implementing the cooperative learning model can improve student learning outcomes.